KUALITAS PRODUK BERPENGARUH POSITIF DAN SIGNIFIKAN TERHADAP KEPUTUSAN PEMBELIAN - Munafis, Subhan (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The research was conducted at the LN shop in CV. NB which is located on Jl. Semboja, Kebon Kopi Village, Bogor Tengah District, Bogor City for 6 months with the analytical approach used is quantitative. The population is 130 people. The sample for this research was 99 people. The results of the research show that the t test (Partial Test) on the product quality variable is 1.990 with a sig value of 0.005 and ? = 5%, obtained t table = 1.985 so it can be said that the product quality variable has a positive effect and a significant effect. influence on purchasing decisions at Lazada Nairastore. The service quality variable has a significant value of 2.316 with a sig value of 0.003 and ? = 5%, obtained ttable = 1.985 so it can be concluded that service quality has a positive and significant effect on purchasing decisions at Lazada Nairastore. Meanwhile, simultaneously product quality and service quality have a positive and significant effect on purchasing decisions with the F test results obtained by fcount = 4.710 which is greater than the ftable for ? = 5% of 3.088 and a significant value of 0.011 which is less than 0.05.